The Technique is the New Subject of History: Technological Posthumanism and the Twilight of the Human (Revista Iberoamericana de Bioética, 2021)
The pandemic generated by the SARS-CoV-2 virus has accelerated digital transformation processes. To understand how technology holds sway over our societies, it is necessary to return to its conditions of possibility. These conditions respond to a certain metaphysics that was born, transformed, intensified and improved, concluding in a sort of omni-embracing language. However, technological transformation affects not only the planet, but also human beings. Within this context, the human being becomes obsolete, and a new subject of history appears, the technique. Technological posthumanism or transhumanism is the ideology that maintains and engages this new subject.
Keywords: transhumanism; Fourth Industrial Revolution; humanism; technology; posthumanism